Mengungkapkan Pembelian Impulsif Pengguna Marketplace Shopee: Peran Potongan Harga, E-WOM dan Motivasi Belanja Hedonis - Viviani, Olinda; Aries Setiawan; Mahmud Mahmud; Herry Subagyo (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of Price Discount, E-WOM, Hedonic Shopping Motivation on Impulse Buying at Marketplace Shopee (Study case of Dian Nuswantoro University). The population of this research is Dian Nuswantoro University who have purchased at marketplace Shopee. Sampling technique used is questionnaire method and amounted to 100 respondents. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that the variables of Price Discount doesn’t have a significant influence on Impulse Buying, while E-WOM and Hedonic Shopping Motivation have a significant influence on Impulse Buying partialy. Variables of Price Discount, E-WOM and Hedonic Shopping Motivation have a significant influence on Impulse Buying simultaneously.